Private Equity Valuation and IRR Algorithm - Arnold, Tom; Marshall, Cassandra D.; Meng, Bo (Journal of Accounting and Finance, 2024)
An algorithm is developed that calculates the IRR for various private equity entities within a private equity leveraged transaction. The algorithm calculates the total anticipated value for a transaction and then produces the associated IRRs based on the exit EBITDA, the EBITDA multiple, and the available cash. The benefits of the algorithm are that multiple programming formats become available, insights emerge that are difficult to perceive using an equivalent spreadsheet pro forma analysis, and other types of analyses become possible for examining individual parameters.